1986
DOI: 10.2307/1541383
|View full text |Cite
|
Sign up to set email alerts
|

GROWTH AND SEXUAL MATURATION OF LABORATORY-CULTURED MONTEREYBOTRYLLUS SCHLOSSERI

Abstract: Growth and sexual maturity were compared among Monterey Botryllus schlosseri colonies cultured in the laboratory and in Monterey Marina in two separate studies: Phase I April to July 1984, a time when Botryllus growth is rapid in the field, and Phase II December 1984 to March 1985, a time when growth is minimal in the field. Laboratory colonies were kept in tanks of standing, aerated filtered seawater at 15C, 20C, and 24C; the seawater was changed daily or on alternate days. Food types were two concentrations … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
65
0

Year Published

1988
1988
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 103 publications
(72 citation statements)
references
References 13 publications
2
65
0
Order By: Relevance
“…First, Sabbadin and Zaniolo demonstrated that progenitors are mobile, and can naturally transplant between parabiosed individuals resulting in long-term germline chimerism and parasitism (Sabbadin and Zaniolo, 1979). Second, adults in both natural and laboratory-reared populations cycle between fertile and infertile states, demonstrating that germline progenitors that can be quiescent exist within an individual (Boyd et al, 1986;Sabbadin, 1953). Finally, prospective isolation studies suggested that both germline and somatic progenitors could be enriched about 10 times based on ALDH activity (Laird et al, 2005).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…First, Sabbadin and Zaniolo demonstrated that progenitors are mobile, and can naturally transplant between parabiosed individuals resulting in long-term germline chimerism and parasitism (Sabbadin and Zaniolo, 1979). Second, adults in both natural and laboratory-reared populations cycle between fertile and infertile states, demonstrating that germline progenitors that can be quiescent exist within an individual (Boyd et al, 1986;Sabbadin, 1953). Finally, prospective isolation studies suggested that both germline and somatic progenitors could be enriched about 10 times based on ALDH activity (Laird et al, 2005).…”
Section: Discussionmentioning
confidence: 99%
“…Botryllus schlosseri colonies were raised, staged, crossed and screened at 18-20°C according to Boyd et al (Boyd et al, 1986). Embryos were isolated and prepared for in situ hybridization as previously described (Brown and Swalla, 2007).…”
Section: Animalsmentioning
confidence: 99%
“…This unique developmental phenomenon, in which every week all functional soma go through an apoptotic process, remains an empirical and theoretical challenge. To date, only a limited number of methodologies have been found to successfully alter the blastogenic rhythm, including changes of water temperature regimen (Boyd et al, 1986;, use of allogeneic fusions (Rinkevich and Weissman, 1987a), or zooid/bud removals (Sabbadin, 1956a,b;Lauzon et al, 2002) or by employing ionization radiation (Rinkevich and Weissman, 1990). All the above protocols, however, had not revealed much of the nature of this unique phenomenon.…”
mentioning
confidence: 99%
“…The colonial ascidians B. schlosseri and B. leachi can be readily cultured on glass slides in the laboratory (generation time 2-3 months) (Boyd et al, 1986). These animals, which produce few embryos, are particularly adapted to the study of blastogenesis and regeneration.…”
Section: Experimental Techniques In Tunicatesmentioning
confidence: 99%
“…The breeding of C. intestinalis and C. savignyi in the laboratory (Hendrickson et al, 2004;Joly et al, 2007) has also permitted the development of germ-line transgenesis by electroporation (Matsuoka et al, 2005), a technique that has been subsequently improved by the use of the Minos transposon, which opens the way to insertional mutagenesis and enhancer-trap assays . Finally, powerful computational methods and infrastructures have been developed for solitary ascidians, in particular C. intestinalis, which facilitate genomic data analysis and the integration of molecular and anatomical data into virtual representations of embryogenesis (Tassy et al, 2010;Endo et al, 2010).The colonial ascidians B. schlosseri and B. leachi can be readily cultured on glass slides in the laboratory (generation time 2-3 months) (Boyd et al, 1986). These animals, which produce few embryos, are particularly adapted to the study of blastogenesis and regeneration.…”
mentioning
confidence: 99%